LANDSEKAP PERTAMANAN: KAJIAN ATAS DATA TEKSTUAL - Aziz, Fadhila Arifin (Berkala Arkeologi, 1994)
The use of textual data can be considered as evidence of cultural testimony in accordance with the events and circumstances of that time. Textual data in the form of inscriptions as a source of written history can also be considered as a reflection of social facts that come from ideas (cognition) and collective behavior of a group of people with a certain cultural background. In-depth exploration and study of the contents of the inscription will enrich both epigraphic knowledge itself and ancient Indonesian history.